2019
DOI: 10.1002/asi.24138
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for self‐archiving on an academic social networking site: A study on researchgate

Abstract: This study investigates motivations for self‐archiving research items on academic social networking sites (ASNSs). A model of these motivations was developed based on two existing motivation models: motivation for self‐archiving in academia and motivations for information sharing in social media. The proposed model is composed of 18 factors drawn from personal, social, professional, and external contexts, including enjoyment, personal/professional gain, reputation, learning, self‐efficacy, altruism, reciprocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 43 publications
0
38
0
1
Order By: Relevance
“…They found that researchers prefer short answers with positive action-oriented statements, revealing a pragmatic approach oriented at finding solutions to specific problems. Lee and colleagues conducted a survey among ResearchGate users on the motivations for using the platform by considering factors from personal, professional, social and external contexts [48]. They found that accessibility of knowledge was the main reason for using the system.…”
Section: Scientific Social Networking Sites Knowledge Sharing and Knmentioning
confidence: 99%
“…They found that researchers prefer short answers with positive action-oriented statements, revealing a pragmatic approach oriented at finding solutions to specific problems. Lee and colleagues conducted a survey among ResearchGate users on the motivations for using the platform by considering factors from personal, professional, social and external contexts [48]. They found that accessibility of knowledge was the main reason for using the system.…”
Section: Scientific Social Networking Sites Knowledge Sharing and Knmentioning
confidence: 99%
“…They found that researchers prefer short answers with positive action-oriented statements, revealing a pragmatic approach oriented at finding solutions to specific problems. Lee and colleagues conducted a survey among Researchgate users on the motivations for using the platform [46]. They found that accessibility of knowledge was the main reason for using the system.…”
Section: Scientific Social Networking Sites Knowledge Sharing and Knmentioning
confidence: 99%
“…SSNSs provide researchers with powerful means to find solutions to specific difficulties met during their work [40; 42; 45]. As a repository a SSNS provide easy access to publications and other documents [46]. Through the questions and answers function they offer the possibility to ask for advice to solve specific problems [40].…”
Section: Research Modelmentioning
confidence: 99%
“…This presentation will briefly introduce a recent study about researchers' motivations for self‐archiving their information on ResearchGate. Self‐archiving is defined as “the action of uploading any kind of academic work, material, or research data to personal websites or institutional or subject repositories to make them freely available to and accessible by the public online” (Lee et al, ). We proposed a motivational framework including 18 factors, including enjoyment, personal and professional gain, reputation, learning, self‐efficacy, altruism, reciprocity, trust, community interest, social engagement, publicity, accessibility, self‐archiving culture, influence of external actors, credibility, system stability, copyright concerns, and additional time and effort.…”
Section: Panel Organization and Formatmentioning
confidence: 99%
“…In recent years, academic social networking sites (ASNSs) are being adopted as a new scholarly communication platform by individual academics that reflects a combination of academic capital and social networking skill (Gruzd et al, 2012;Thelwall & Kousha, 2015). Researchers have utilized ASNSs not only to discover, read, share, and archive publications, but also to seek and share research information, build networks, and present professional images (Arshad & Ameen, 2017;Bianchini, 2012;Dermentzi, Papagiannidis, Toro, & Yannopoulou, 2016;Lee, Oh, Dong, Wang, & Burnett, 2019;Xia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%